The cooperation of Fe3C nanoparticles with isolated single iron atoms to boost the oxygen reduction reaction for Zn–air batteries - Zhou, Fangling; Peng Yu‡; Sun, Fanfei; Zhang, Guangying; Liu, Xu; Wang, Lei (Journal of materials chemistry. A, Materials for energy and sustainability, 2021)
Fe–N–C exhibits excellent electrocatalytic oxygen reduction reaction (ORR) activity, but the synergistic effect between metallic and isolated iron species remains unclear. Herein, N-doped carbon nanostructure encapsulated Fe3C nanoparticles coupled with atomically dispersed Fe–N4 (Fe3C–FeN/NC) were synthesized by a general pyrolytic strategy. The introduction of Zn species promoted the formation of Fe–N4 during pyrolysis. Theoretical calculations indicated that the oxygen adsorption capacity of Fe3C was further enhanced by Fe–N4, which facilitated the breakage of O–O bonds. As a result, its onset potential of 0.95 V surpassed that of Fe3C/NC (0.89 V) and NC (0.85 V) in 0.1 M KOH electrolyte. Only a 7 mV negative shift was obtained after 5000 cycles, which outperformed Pt/C catalysts. The assembled primary Zn–air battery (ZAB) displayed a high open-circuit potential of 1.41 V and a maximum power density of 166 mW cm−2 with an excellent specific capacity of 745 mA h g−1, outperforming the battery assembled with a commercial Pt/C catalyst.